BUSINESS PLAN OF MAKE UP ARTIST BYGITAHRS - Haris, A Gita Namira Patigana; Iskandar, Budi Permadi (Journal of Business and Management, 2018)
Abstract. Make-up artist is one of the business that nowadays have a high demand in the market. Nowadays there are so many new make-up artist comes up in the market. Bygitahrs is one of the new makeup artist in Bandung. Because there are so many competitors, Bygitahrs wishes to gain more sales and make their market share bigger by taking competitive advantage. Before the business can go further and create a business plan, it must do some analysis. This analysis is to identify the problems which they are currently facing or will face in the future. The purpose of this study is to prepare and create a business plan that can be simply applied by Bygitahrs. The preparation step of the business plan is started by doing company analysis, market analysis, and competitors analysis which are based on primary research and secondary research, but mostly build upon the primary research, The data from the analysis will be used to process a new strategy for the business. The strategy used is growth hacking strategy because it is found to make the business more effective and be able to grow significantly in a short period. The list of programs, which planned specifically already are photoshoot, upgrading skills, regular post, endorsement, giveaway, cashback, collaboration, tutorial make up, and insta-story sharing This business plan will use Rp24.500.000. from Bygitahrsâ€™s profit in 2017. After sort of calculation, Bygitahrs will have Rp315.000.000 of Gross Profit and Rp138.400.000 as the Total Expense. By the end of December 2018, Bygitahrs will get Rp176.600.000 as her Net Profit.Â Keywords: Make Up Artist, Business Plan, Growth Hacking